Infected abdominal aortic aneurysm due to Escherichia coli. Issue 3 (4th May 2017) - Bouzas, Miguel; Tchana-Sato, Vincent; Lavigne, Jean Paul
Abstract: Early diagnosis of infected abdominal aortic aneurysm (IAAA) is still a medical challenge due to its diverse and non-specific symptoms and signs. The most common responsible pathogens are Salmonella, Staphylococcus, Campylobacter and Streptococcus species. The authors report the case of a 67-year-old man, admitted for high fever and finally diagnosed with Escherichia coli ( E.coli )-related IAAA. The IAAA ruptured during the general anaesthesia induction, leading to an emergency surgery. The authors successfully proceeded to an open aneurysmectomy with extensive debridement and in situ graft replacement. This case emphasizes the potential for rapid IAAA expansion, its high-rupture risk and the importance of computed tomography as a diagnostic tool.